2018
DOI: 10.1007/s00198-018-4535-4
|View full text |Cite
|
Sign up to set email alerts
|

Fermented dairy products consumption is associated with attenuated cortical bone loss independently of total calcium, protein, and energy intakes in healthy postmenopausal women

Abstract: ISRCTN11865958 ( http://www.isrctn.com ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The study also showed a slight protective effect of the consumption of dairy products for hip fracture [30]. Biver et al conducted a three-year observation on the consumption of dairy fermented products in postmenopausal women [31]. Reduced bone loss was found in women consuming fermented dairy products, regardless of calcium, protein or energy intake.…”
Section: Effects On the Risk Of Cardiovascular Eventsmentioning
confidence: 93%
See 4 more Smart Citations
“…The study also showed a slight protective effect of the consumption of dairy products for hip fracture [30]. Biver et al conducted a three-year observation on the consumption of dairy fermented products in postmenopausal women [31]. Reduced bone loss was found in women consuming fermented dairy products, regardless of calcium, protein or energy intake.…”
Section: Effects On the Risk Of Cardiovascular Eventsmentioning
confidence: 93%
“…Reduced bone loss was found in women consuming fermented dairy products, regardless of calcium, protein or energy intake. This phenomenon was not observed in women consuming mainly milk or ripening cheeses [31]. Researchers suspect that the positive effects of fermented dairy products consumption may result from the presence of probiotics [31].…”
Section: Effects On the Risk Of Cardiovascular Eventsmentioning
confidence: 99%
See 3 more Smart Citations